Audio Visual Media Learning Guidance using Wondershare Filmora as Elementary School Teacher Professional Development in Batupoaro District Baubau City - Yusnan, Muhammad; Aminu, Nurmin (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
The field of Information Technology which is the basis of learning, in this case the basis of the Teacher Working Group is obliged to share about video editing procedures with Filmora. In addition, the existence of a Teacher Working Group organization in Batupoaro District is also a strong reason to help schools that have not yet received an understanding of the Wondershare Filmora software. The method used in this service activity is in the form of socialization and practice. Through training and guidance, it is hoped that the Teacher Working Group in Batupoaro District can make Wondershare Filmora software as a good learning medium to be applied in elementary schools. The results of this service activity are marked by increased knowledge, understanding and skills of the Teacher Working Group Batupoaro Cluster 2 Baubau City has: 1) a better understanding of multimedia, especially in terms of video editing, 2 becomes more aware of applicable information technology, 3) become more aware of the Wondershare Filmora software application in daily learning classes, 4) become more confident when entering the community with the knowledge they have